A structural inventory of native ribosomal ABCE1‐43S pre‐initiation complexes. (8th December 2020) - Kratzat, Hanna; Mackens‐Kiani, Timur; Ameismeier, Michael; Potocnjak, Mia; Cheng, Jingdong; Dacheux, Estelle; Namane, Abdelkader; Berninghausen, Otto; Herzog, Franz; Fromont‐Racine, Micheline; Becker, Thomas; Beckmann, Roland
Abstract: In eukaryotic translation, termination and ribosome recycling phases are linked to subsequent initiation of a new round of translation by persistence of several factors at ribosomal sub‐complexes. These comprise/include the large eIF3 complex, eIF3j (Hcr1 in yeast) and the ATP‐binding cassette protein ABCE1 (Rli1 in yeast). The ATPase is mainly active as a recycling factor, but it can remain bound to the dissociated 40S subunit until formation of the next 43S pre‐initiation complexes. However, its functional role and native architectural context remains largely enigmatic. Here, we present an architectural inventory of native yeast and human ABCE1‐containing pre‐initiation complexes by cryo‐EM. We found that ABCE1 was mostly associated with early 43S, but also with later 48S phases of initiation. It adopted a novel hybrid conformation of its nucleotide‐binding domains, while interacting with the N‐terminus of eIF3j. Further, eIF3j occupied the mRNA entry channel via its ultimate C‐terminus providing a structural explanation for its antagonistic role with respect to mRNA binding. Overall, the native human samples provide a near‐complete molecular picture of the architecture and sophisticated interaction network of the 43S‐bound eIF3 complex and the eIF2 ternary complex containing the initiator tRNA. Synopsis: Function and native architecture of ribosomal complexes with recycling factor ATPase ABCE1 have remained unclear. Here, a cryo‐EM‐based structural inventory of native ABCE1‐bound translation initiation complexes from human and yeast reveal a novel hybrid conformation of the ABCE1 stabilized by a dimer of translation initiation factor eIF3j. Cryo‐EM structures reveal the near‐complete molecular architecture of eIF3 and eIF2 ternary complexes in the context of the 43S pre‐initiation complex. Under native conditions, ABCE1 is present in all captured stages of translation initiation and displays a hybrid conformation with ADP and ATP bound concurrently. In the new ABCE1 conformation, an eIF3j dimer stabilizes the nucleotide binding site of ABCE1 and occludes the mRNA entry channel via the C‐terminus of one monomer. Abstract : Cryo‐EM structures of native human and yeast translation initiation complexes reveal a novel hybrid conformation of the recycling factor ATPase ABCE1, which is stabilized by a dimer of translation initiation factor eIF3j.